Influence of Account Receivable Management Practices on the Performance of Small and Medium Scale Enterprises - Sah, Genesis Gyasi (Technium Social Sciences Journal, 2022)
The business enterprise sector has been known as a key supporter in the achievement of the economic evolution in the world at large nowadays. The small and medium scale enterprise in particular have attracted the attention of many governments in our world of today as a key source of employment and economic steadiness.Small and medium enterprises (SMEs) play an important role in the economic growth in Ghana. SMEs contribute to economic development in various ways: by creating employment for rural and urban growing labour force, providing desirable sustainability and innovation in the economy as a whole. The success or failure of new business is often dependent on overcoming a series of potential barriers, such as securing financial backing, adequate and appropriate guidance and training (Fielden et al, 2000). In line of these challenges, this paper sought to evaluate the influence of receivable management on performance of small and medium scale enterprises in Kumasi Metropolis in Ghana.This study adopted a descriptive design with cross sectional survey. According to Churchill (2011), cross sectional survey affords the researcher to capture the relevant information from almost all the key stakeholders within the SMEs across the Metropolis to be able to do a critical assessment. The study sought to collect data from the SMEs at one point in time and determine the impact of management accounting practices on financial performance of SMEs in in the Kumasi Metropolis in Ghana. The study established Receivable management practices were effectively followed by the selected SMEs, and there was a statistical significant effect of receivable management practices on firm performance.